Influência da n-acetilcisteína no crescimento e viabilidade de folículos pré-antrais bovinos cultivados in vitro - Nascimento, Danisvânia Ripardo (2022)
The oxidative stress during in vitro culture of preantral follicles is one of the factors responsible for the reduction of follicular viability. Thus, it is necessary to supplement the culture media with antioxidant substances. The N-acetylcysteine (NAC) acts directly on free radicals and indirectly through the production of glutathione (GSH). This study aims to investigate the effects of different concentrations of N-acetylcysteine (NAC) on growth, morphology, antrum formation, and viability of bovine secondary follicles cultured in vitro for 18 days. To this end, follicles were cultured at 38.5°C with 5% CO2 for 18 days in TCM-199+ alone or supplemented with 1.0, 5.0 or 25.0mM NAC. Follicular growth, morphology, antrum formation, viability (calcein-AM and ethidium homodimer-1), and histological features were evaluated at the end of culture. Follicular diameter and fluorescence intensity data for viability were analyzed by Kruskal-Wallis test, followed by Dunn's multiple comparison test. Percentages of follicle survival and antrum formation were compared by the chi-square test and percentages of growing follicles were compared by Fisher's exact test (P<0.05). The results showed that 1.0 mM NAC significantly increased the percentage of growing follicles when compared to other treatments. The addition of 5.0 mM of NAC did not change significantly in any parameter. On the other hand, 25.0 mM NAC significantly reduced the rate of growing follicles. Secondary follicles cultured with 1.0 mM NAC had higher fluorescence intensity for calcein-AM, while those cultured with 25.0 mM NAC were mainly stained with ethidium homodimer-1 (P<0.05). Histological analysis showed that oocyte vacuolization is the first sign of degeneration in cultured follicles. In conclusion, 1.0 mM NAC increases follicle viability and growth rate in bovine secondary follicles cultured in vitro, while 25.0 mM NAC cause damages in cellular membranes and reduces follicular growth rate.